已知不等式X^2-2X-3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 18:44:44
已知不等式X^2-2X-3已知不等式X^2-2X-3已知不等式X^2-2X-3X^2-2X-3a=1,b=-2,a+b=-1,A∩B=(-1,2)a+b=-3x²-2x-3(x+1)(x-3
已知不等式X^2-2X-3
已知不等式X^2-2X-3
已知不等式X^2-2X-3
X^2-2X-3
a=1, b=-2, a+b=-1, A∩B=(-1,2)
a+b=-3
x²-2x-3<0
(x+1)(x-3)<0
-1
X²+X-6<0
(x+3)(x-2)<0
-3
∴A={x|-1
全部展开
a+b=-3
x²-2x-3<0
(x+1)(x-3)<0
-1
X²+X-6<0
(x+3)(x-2)<0
-3
∴A={x|-1
方程可化为:(x+1)(x-2)=0
即:x²-x-2=0
不等式X²+aX+b<0为:x²-x-2<0
∴a=-1,b=-2
∴a+b=-1+(-2)=-3
收起
∵x²-2x-3<0
∴-1
∴-3
∵不等式X^2+aX+b<0的解集A交B
∴-1, 2是x²+ax+b=0
∴1-a+b=0 4+2a+b=0
∴a=-1 b=-2
∴a+b=-3